2006
DOI: 10.1111/j.1527-3466.2006.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Adenosine as Adjunctive Therapy in Acute Myocardial Infarction

Abstract: Although early reperfusion and maintained patency is the mainstay therapy for ST elevation myocardial infarction, experimental studies demonstrate that reperfusion per se induces deleterious effects on viable ischemic cells. Thus "myocardial reperfusion injury" may compromise the full potential of reperfusion therapy and may account for unfavorable outcomes in high-risk patients. Although the mechanisms of reperfusion injury are complex and multifactorial, neutrophil-mediated microvascular injury resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 157 publications
(307 reference statements)
1
75
1
2
Order By: Relevance
“…Acute Myocardial Infarction Study of Adenosine (AMISTAD) clinical trials showed that infusion of adenosine for 3 h resulted in a striking reduction in infarct size [631]. However, long-term stimulation of A2BR commenced after MI prevented cardiac remodelling in rats [632] and contributed to post-infarction heart failure [633].…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…Acute Myocardial Infarction Study of Adenosine (AMISTAD) clinical trials showed that infusion of adenosine for 3 h resulted in a striking reduction in infarct size [631]. However, long-term stimulation of A2BR commenced after MI prevented cardiac remodelling in rats [632] and contributed to post-infarction heart failure [633].…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…causes hypotension and bradycardia because of its vasodilatory and negative chronotropic effects. 22 an experimental infarction study in rats, however, showed that an infusion with PeGylated liposomes augmented the cardioprotective effects of adenosine against ischemia/reperfusion injury and reduced its unfavorable hemodynamic effects.…”
Section: Protection Of Infarcted Myocardium With Liposomal Formulatiomentioning
confidence: 99%
“…In addition, mitochondrial, and sarcolemmal KATP channels are also potential cellular protection targets and continue to be evaluated in clinical studies [101,111]. Adenosine receptors (A1 and A2 subtypes) as well as protein kinase C receptors also continue to be targeted [112][113][114][115]; mitogen activated protein kinase blockers have also been evaluated [116,117]. Pharmacologic treatments aimed at the Reperfusion Injury Salvage Kinase (RISK) and Survivor Activating Factor Enhancement (SAFE) pathways that activate pro-survival pathways possibly by inhibiting opening of mPTP at the level of the mitochondria are being studied [111,[118][119][120][121].…”
Section: Pharmacologic Approachmentioning
confidence: 99%